EPIDEMIOLOGICAL ASSESSMENT OF SMOKING-RELATED HEALTH BURDEN AND CESSATION EFFORTS IN WEST KALIMANTAN: Kajian Epidemiologi Terhadap Beban Kesehatan Akibat Merokok dan Upaya Berhenti Merokok di Kalimantan Barat - Fitriangga, Agus; Alex, Alex (Jurnal Berkala Epidemiologi, 2026)
Background: Indonesia has one of the highest smoking prevalence rates in Southeast Asia, reaching at least 65%, with notable regional differences. Some areas, such as West Kalimantan, continue to exhibit high smoking rates alongside limited cessation services. Purpose: This study aims to evaluate the health risks associated with smoking and determine factors that motivate smokers to quit among residents of Pontianak City and Kubu Raya District in West Kalimantan. Methods: A cross-sectional survey was conducted from June to November 2024 using multistage cluster random sampling. Participants included 385 adults aged 18 years and older who were surveyed regarding their smoking habits and health conditions. Important factors were identified and assessed using logistic regression and ROC curve analyses. Results: The prevalence of smoking was higher in Kubu Raya than in Pontianak (41.18% vs. 36.13%). Chronic respiratory symptoms (aOR=3.91; 95% CI: 2.24–6.81) and cardiovascular disease (aOR=3.76; 95% CI: 1.98–7.14) were strong quit attempt predictors. Receiving healthcare advice (aOR=2.33) and holding a higher educational degree (aOR=1.82) also positively affected cessation. The AUC of the model was 0.71, suggesting strong predictive ability. Conclusion: While the focus on smoking-related illnesses helps motivate cessation attempts, it emphasizes the need to integrate tobacco cessation services within chronic disease frameworks to advance Sustainable Development Goals 3: Good health and well-being. Strengthening community-specific public health initiatives is essential to enhance understanding and availability of cessation support in underserved areas.